STRATEGIES OF KNOWLEDGE MANAGEMENT PROCESSES AND ITS EFFECT ON THE PERFORMANCE MARKETING AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF WORKERS IN A NUMBER OF RETAIL STORES (World Bulletin of Management and Law, 2022)
This research aims to demonstrate the impact of the application of Strategies of Knowledge management Processes and their impact on marketing performance through the ability of organizations to integrate marketing activities in a scientific and practical framework with the system of knowledge management strategies, which will make the organization able to build and store an intellectual accumulation that increases its ability to adopt innovative strategies for elements The marketing mix is based on knowledge in dealing with market variables to achieve competitive advantage. The researcher chose a group of retail stores as a field for his study, Data and information were collected by means of a questionnaire prepared for this purpose, in addition to the personal interviews that were conducted with them.4) Sub-hypotheses, which were tested by a set of descriptive statistics tools represented by (percentages, frequencies, arithmetic mean, standard deviation) and inferential statistical tools represented by (Spearman correlation coefficient, simple linear regression coefficient) as the researcher used the Amos statistical application to determine the effect value , The researcher reached a set of conclusions, the most prominent of which was the lack of clarity of vision for store departments with the concepts of knowledge management and management Than mirror On weakness Development operations Knowledge management and rally Resources necessary For this Activity to make it Appropriate and compatible With the changes environmental, On the basis of his findings, the researcher developed a set of recommendations, the most important of which are the necessity interest With knowledge to have a clear vision of the concepts of knowledge management and to adopt appropriate methods for knowledge management, the most important of which is the use of information technology in knowledge management processes, to be able From Adaptation With the changes environmental Especially since the environment of these organizations is characterized by movement and dynamism.